New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East - Kopylov, D.s.; Spasojevic, T.; Klopfstein, S. (Zootaxa, 2018)
Ichneumonidae constitute one of the largest families of organisms, but their fossil record is severely understudied, which precludes inferences about their early evolutionary history. We here describe a new genus and two new species of ichneumonids from the Early Eocene Tadushi Formation (Russian Far East). The new taxa are Crusopimpla tadushensis gen. et sp. nov. and Dolichomitus? saxeus sp. nov. Pimpla rediviva (Brues) is redescribed and placed in the genus Crusopimpla. This new genus is unique within Pimplinae in having a completely developed propodeal carination and probably represents one of its most basal lineages. Using a phylogenetic hypothesis of the subfamily, we discuss potential pathways of morphological evolution in the group, which will provide a basis for future placement of pimpline fossil taxa.